2020
DOI: 10.11114/aef.v7i5.4927
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Investment Decisions: A Study of Individual Investors on the Zimbabwe Stock Exchange

Abstract: This study investigated factors that inform individual investors in their decision-making on the Zimbabwe Stock Exchange. The main objective was to identify and assess the effect of the behavioural factors on investment decisions of individual investors. A quantitative survey of 291 randomly selected individual Zimbabwe Stock Exchange investors was conducted. Multiple regression analysis was used to calculate the correlation coefficient of behavioural factors and investment decision while correlation analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
2
8
1
2
Order By: Relevance
“…Referring to the prospect theory, this is possible because investors think that the investment made is more like a choice between the gain and loss of investment. The results of this study support the research conducted by Aziz & Khan (2016), but does not support the results of research conducted by Cherono et al, (2019); Hunguru et al (2020); Isidore R & Christie (2019); Jain et al, (2019);S Hallale & Gadekar (2019). This difference is possible due to cultural differences, differences in the age of respondents, and differences in existing technological developments so that technological advances have an important role in disseminating information to investors.…”
Section: Overconfidence (O)contrasting
confidence: 95%
See 2 more Smart Citations
“…Referring to the prospect theory, this is possible because investors think that the investment made is more like a choice between the gain and loss of investment. The results of this study support the research conducted by Aziz & Khan (2016), but does not support the results of research conducted by Cherono et al, (2019); Hunguru et al (2020); Isidore R & Christie (2019); Jain et al, (2019);S Hallale & Gadekar (2019). This difference is possible due to cultural differences, differences in the age of respondents, and differences in existing technological developments so that technological advances have an important role in disseminating information to investors.…”
Section: Overconfidence (O)contrasting
confidence: 95%
“…In the related analysis, Samuelson & Zeckhauser (1988) introduced the term "status quo bias" after documenting the tendency to maintain the status quo in decision making. Previous research examining the relationship of loss aversion to investment decisions has had various results such as Cherono et al (2019); Hunguru et al (2020); Isidore R & Christie (2019) shows a significant relationship of loss aversion to investment decisions, and S Hallale & Gadekar (2019) indicates a weak relationship, meanwhile Aziz & Khan (2016); and Jain et al (2019) results that there is no relationship between loss aversion and investment decisions. Furthermore, in this study will discuss these financial behaviors towards community investment decisions, especially investments in capital market.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the research conducted in the Zimbabwe stock market, the following psychological biases have a role in investment decisions: anchoring, availability, gambler's fallacy, overconfidence, herding, loss aversion, mental accounting, regret aversion, and representativeness (Hunguru et al, 2020). The study in Nepal indicated that heuristics (such as anchoring, representative, overconfidence, and availability bias) have little bearing on investment returns (Pokharel, 2020); according to the research, anchoring and adjustment bias impact project selection directly or indirectly.…”
Section: Anchoring and Adjustment Biasmentioning
confidence: 99%
“…Dalam mengambil keputusan investasi, Generasi Z tentu dipengaruhi oleh beberapa faktor [16]. Faktor tersebut diantaranya ialah faktor demografi, literasi keuangan, bias perilaku, persepsi risiko dan persepsi toleransi [17].…”
Section: Keputusan Investasiunclassified